HEALTH-STATE VARIABLES AND ENZYMATIC BIOMARKERS AS SURVIVAL PREDICTORS IN NESTLING GREAT TITS (PARUS MAJOR): EFFECTS OF ENVIRONMENTAL CONDITIONS - Norte, A; Ramos, J; Araujo, P; Sousa, J; Sheldon, B (2008)
The health state of nestlings can be a useful bioindicator of the quality of the environment in which they are reared, but, to enable detection of responses to environmental change, the variation of health parameters under natural conditions should be evaluated. We describe the variation of morphological, biochemical, and hematological variables in relation to time of sampling, hatching date, brood size and type, and year in nestlings of two populations of Great Tits (Parus major) in Choupal, Portugal, and Wytham, United Kingdom. The influence of these health variables on nestlings' survival to first winter and recruitment into the breeding population was assessed in Wytham. Variation in plasma protein, total plasma cholinesterase (ChE), and acetylcholinesterase activities reflected circadian rhythms. Hatching date affected total plasma ChE and butyrylcholinesterase (BuChE) activities, and levels of red-blood-cell hemoglobin (Hb) and hematocrit (HCT). In Choupal, HCT increased with brood size. Nestlings in Choupal had significantly lower protein and Hb levels, and higher glutathione peroxidase (GSH-Px) activity, during a drier year. Second-brood nestlings had significantly lower levels of Hb and HCT. Of the studied variables, only plasma BuChE and red-blood-cell GSH-Px activities were related to nestlings' survival to first winter and recruitment. © 2008 by The American Ornithologists' Union. All rights reserved.